Intergenerational support shaping residential trajectories: Young people leaving home in a gentrifying city. (February 2017) - Hochstenbach, Cody; Boterman, Willem R
Parental support, in both financial and non-financial ways, is important in explaining the residential trajectories of young people leaving home. For instance, the influence of parental support on the ability to leave home or enter homeownership is well established. This study adds a dimension by investigating how inequalities in terms of parental background – particularly assets – are spatially articulated. More specifically, we study whether parental background influences the types of neighbourhoods young people leaving home move to. Drawing on the case of Amsterdam, we show that these 'fledglings', despite their generally very modest income, disproportionally move to gentrification neighbourhoods. Moreover, fledglings with wealthy parents are even more likely to move to both early gentrifying and expensive mature-gentrification neighbourhoods. Gentrification research should therefore also take into account the importance of middle class social reproduction strategies as well as the potential intergenerational transfer of (financial) resources – rather than merely personal financial situation – in shaping housing outcomes and spatial inequalities of young people leaving home. Drawing on parental support, young people may be able to outbid other households and hence exclude them from gentrifying neighbourhoods. Consequently, parental wealth and other resources can thus contribute to gentrification and exclusion.